2009
DOI: 10.1080/09537100802657735
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Platelet Mapping™ Assay on rotational thromboelastometry ROTEM®

Abstract: Rotational thromboelastometry ROTEM is available as point-of-care coagulation monitoring in an increasing number of European operating theatres and emergency rooms. The Platelet Mapping Assay has been described as a platelet aggregation assay for thromboelastography TEG. The aim of this experimental trial was to evaluate feasibility of the Platelet Mapping Assay on the ROTEM test system. Whole blood was drawn from 22 adult volunteers and patients with and without antiplatelet medication. Platelet aggregability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 24 publications
0
34
0
2
Order By: Relevance
“…3,32 All assays were processed on the ROTEM equipment. We assumed there would be limited differences between applying ROTEM or TEG analyzers, as has been forwarded in recent studies, 43 but minor dissimilarities cannot be excluded. In the current study design, it was not possible to address clinical outcome parameters or aspects of health economics.…”
Section: Discussionmentioning
confidence: 99%
“…3,32 All assays were processed on the ROTEM equipment. We assumed there would be limited differences between applying ROTEM or TEG analyzers, as has been forwarded in recent studies, 43 but minor dissimilarities cannot be excluded. In the current study design, it was not possible to address clinical outcome parameters or aspects of health economics.…”
Section: Discussionmentioning
confidence: 99%
“…The primary uses to date for TEG PlateletMapping include monitoring platelet inhibition therapy and diagnosing naturally occurring thrombocytopathies; however, this novel technique may also be able to identify platelet hyperreactivity 105 . Recently, PlateletMapping was also validated for use in ROTEM analyzers 106 …”
Section: Clinical Applications In Veterinary Medicinementioning
confidence: 99%
“…Unlike platelet function tests, these instruments have been traditionally utilized within surgical and anesthesiology departments as POC tests for determining the risk of bleeding and as a guide to transfusion requirements [138,144]. Recent studies have shown the potential of TEG for monitoring clopidogrel [139,145,146].…”
Section: Pfa-100/200mentioning
confidence: 99%
“…With the PlateletMapping TM system, arachidonic acid and ADP can be used as agonists to pre-activate platelets within the TEG system, thus making the assay theoretically suitable to monitor antiplatelet drugs, although the test lacks sensitivity to detect moderate changes in platelet function [95,138,139]. TEG Õ /ROTEM tests are relatively rapid to perform (<30 min) and have traditionally been used as POC tests in surgical departments.…”
Section: Pfa-100/200mentioning
confidence: 99%